1999
DOI: 10.1046/j.1439-0418.1999.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artemisia annua oil on development and reproduction of Dysdercus koenigii F. (Hem., Pyrrhocoridae)

Abstract: The effect of topical application of Artemisia annua oil on the development and reproduction of Dysdercus koenigii was studied. On the basis of 48 h mortality, the LD50 for fifth instar nymphs was 0.48 μl/nymph. The treated nymphs showed 2 days delay in development, and also produced intermediates. The treatment decreased haemolymph protein concentration and disturbed its electrophoretic protein pattern. The adults which emerged from treated nymphs showed poor ovary development. There was a greater median neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 7 publications
(5 reference statements)
0
6
0
1
Order By: Relevance
“…Para isso, foram selecionadas plantas encontradas no Ceará, em função de as mesmas apresentarem pelo menos uma das seguintes características: a) atribuições de propriedades repelentes segundo crendice popular, b) ação inseticida (Laurent et al 1998, Rao & Subrahmanyam 1999 e c) atividade terapêutica (Matos 1994), neste caso possuindo a vantagem de serem benéficas ao homem. Extração e Análise dos Óleos Essenciais.…”
Section: Palavras-chave: Dengue Extrato De Planta Controle Mosquitounclassified
“…Para isso, foram selecionadas plantas encontradas no Ceará, em função de as mesmas apresentarem pelo menos uma das seguintes características: a) atribuições de propriedades repelentes segundo crendice popular, b) ação inseticida (Laurent et al 1998, Rao & Subrahmanyam 1999 e c) atividade terapêutica (Matos 1994), neste caso possuindo a vantagem de serem benéficas ao homem. Extração e Análise dos Óleos Essenciais.…”
Section: Palavras-chave: Dengue Extrato De Planta Controle Mosquitounclassified
“…The essential oil of A. annua has been found to influence the ovarian development, median neurosecretary cells activity, and haemolymph proteins with nymphal mortality, and insect growth regulator activity in Dysdercus koenigii Fabr. (Hemiptera: Pyrrhocoridae) (Rao et al 1999), and to exhibit repellent and toxicity against stored insect pests, Callosobruchus maculatus and Tribolium castaneum (Shakil et al 2000).The glandular trichomes of A. annua shoots are reported to contain possible plant biopesticides (Dayan & Duke 2003). Artemisia annua extract and artemisinin have also shown their bioactivity against Epilachna paenulata Germ.…”
Section: Introductionmentioning
confidence: 99%
“…Our extracts from C. cyanus [105] and C. jacea [106] showed little if any activity. It was also reported that extracts from the genus Artemisia showed manifold insecticidal effects: general toxicity and disturbance of development and reproduction (Rao et al 1999) or repellent and antifeedant properties (Ignatowicz and Gersz 1997;Tripathi et al 2001). In our experiments, however, extracts of the two tested species, A. vulgaris [95] and A. absinthium [96], had few effects.…”
Section: Discussionmentioning
confidence: 42%